2017
DOI: 10.18632/oncotarget.20682
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and gender modify the effect of TWIST on patient survival in head and neck squamous carcinoma

Abstract: PurposeTWIST is a critical factor for predicting prognosis in several human cancers. Here, we study the prognostic significance of TWIST1 and TWIST2 in Head and Neck squamous cell carcinoma (HNSCC) as well as interactions of TWISTs with both gender and smoking in patient survival.Methodsupper quartile normalized RNA-seq V2 RSEM values of TWIST1 and TWIST2 expressions were retrieved from a TCGA HNSCC dataset. Kaplan-Meier survival curves were used to assess the associations of TWIST1 and TWIST2 with patient sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…KL has also been reported to inhibit TGF-β1-induced epithelial–mesenchymal transition (EMT) by directly binding to TGF-β receptor 29. Our previous study revealed that high expression of TWIST1, a key regulator in EMT, was associated with poor survival in HNSCC 30. In this study, we observed a significantly positive relationship between KL mRNA levels and the overall survival of HNSCC patients.…”
Section: Discussionsupporting
confidence: 53%
“…KL has also been reported to inhibit TGF-β1-induced epithelial–mesenchymal transition (EMT) by directly binding to TGF-β receptor 29. Our previous study revealed that high expression of TWIST1, a key regulator in EMT, was associated with poor survival in HNSCC 30. In this study, we observed a significantly positive relationship between KL mRNA levels and the overall survival of HNSCC patients.…”
Section: Discussionsupporting
confidence: 53%
“…Further studies by Zhu et al investigating TWIST interactions with gender and smoking in patient survival revealed that both smoking and gender could modify the effects on the risk of death in HNSCC patients. Their analysis revealed that TWIST1 links to poor survival obvious in either males or smokers than in either female or non-smokers (Zhu et al 2017 ). Additionally, Stoyianni et al used cancers of unknown primary (CUP) as a model for metastatic dissemination to study the prognostic significance of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly believed that epigenetic changes, such as DNA methylation, can drive abnormal gene expression of crucial genes involved in the development and progression of cancer, including prostate cancer (Chen et al, 2014), liver cancer (Feitelson, 2006), head and neck cancer (Worsham et al, 2014), etc. In addition, previous studies also reported that the methylation status of specific genes significantly associated with worse prognosis (Lee et al, 2006;Zhu et al, 2017). Therefore, the methylation-driven genes could serve as attractive prognostic indicator in tumor patients.…”
Section: Discussionmentioning
confidence: 93%